Correlation of Dynamic Cartilage Contact Stress Aberrations with Severity of Instability in Ankle Incongruity - Tochigi, Yuki (2008)
Joint instability is presumed to cause abnormality in cartilage contact mechanics, which accumulatively damages articular surface over years, leading to osteoarthritis. The purpose of this study was to clarify the effect of instability on dynamic cartilage contact mechanics. Using human ankle cadaver specimens, potentially unstable ankles were modeled by introducing a coronally-directed step-off incongruity of the anterior tibial surface and/or by transecting the anterior talofibular ligament. Specimens were subjected to a duty cycle with quasi-physiologic stance-phase motion and loading. AP tibial forces were modulated, causing a controlled, quantifiable ankle subluxation during the duty cycle. Instantaneous changes in local articular contact stresses in the ankle were continuously measured using a thin and flexible pressure transducer. Tests were repeated while varying the tibial surface condition (anatomic, 1mm step-off, and 2mm step-off), both before/after transection of the anterior talofibular ligament, with various AP force magnitudes, so that situations of various degrees of instability were created for each specimen. Instability events occurred in ankles when the step-off incongruity was introduced, with the abnormality in joint kinematics being greater after ligament transection. Contact stress data revealed that these instability events involved distinctly abrupt increases/decreases in local articular contact stresses, and that the degree of abruptness was correlated very nearly linearly with the abnormality in joint kinematics. The severity of cartilage contact stress aberration appeared to be correlated closely with the degree of instability. Given this linear relationship, even small instability events presumably involve appreciable abnormality in dynamic joint contact mechanics.